Instrumenting a virtual reality headset for at-home gamer experience monitoring and behavioural assessment - Moinnereau, Marc-Antoine; Oliveira, Alcyr A.; Falk, Tiago H. (Frontiers in Virtual Reality, 2022)
Measuring a gamer's behaviour and perceived gaming experience in real-time can be crucial not only to assess game usability, but to also adjust the game play and content in real-time to maximize the experience per user. For this purpose, affective and physiological monitoring tools (e.g., wearables) have been used to monitor human influential factors (HIFs) related to quality of experience (QoE). Representative factors may include the gamer's level of engagement, stress, as well as sense of presence and immersion, to name a few. However, one of the major challenges the community faces today is being able to accurately transfer the results obtained in controlled laboratory settings to uncontrolled everyday settings, such as the gamer's home. In this paper, we describe an instrumented virtual reality (VR) headset, which directly embeds a number of dry ExG sensors (electroencephalography, EEG; electrocardiography, ECG; and electrooculography, EOG) to allow for gamer behaviour assessment in real-time. A protocol was developed to deliver kits (including the instrumented headset and controllers, laptop with the VR game Half-life Alyx, and a second laptop for data acquisition) to participants' homes during the COVID-19 lockdown. A brief videoconference session was made to provide the participants with instructions, but otherwise the experiment proceeded with minimal experimenter intervention. Eight participants consented to participate and each played the game for roughly 1.5 hours. After each gaming session, participants reported their overall experience with an online questionnaire covering aspects of emotions, engagement, immersion, sense of presence, motion sickness, flow, skill, technology adoption, judgement and usability. Here, we describe our obtained findings, as well as report correlations between the subjective ratings and several QoE-related HIFs measured directly from the instrumented headset. Promising results are reported.